Romeo and/or Juliet : a chooseable-path adventure - North, Ryan 1980- (Riverhead Books, 2016)
"In this choose-your-own-path version of Romeo and Juliet, you choose where the story goes every time you read! What if Romeo never met Juliet? What if Juliet got really buff instead of moping around the castle all day? What if they teamed up to take over Verona with robot suits? Whatever your adventure, you're guaranteed to find lots of romance, lots of epic fight scenes, and plenty of questionable decision-making by very emotional teens. All of the endings-there are over a hundred-feature beautiful illustrations by some of the greatest artists working today, including New York Times bestsellers Kate Beaton, Noelle Stevenson, Randall Munroe, and Jon Klassen. Packed with exciting choices, fun puzzles, secret surprises, terrible puns, and more than a billion possible storylines, Romeo and/or Juliet offers a new experience every time you read it. You can choose to play as Romeo or Juliet (obviously) but you can also play as both of them, or as Juliet's nurse, or, if you're good, you can even unlock a fourth playable character! That's right. We figured out how to have unlockable characters in books. Choose well, and you may even get to write the world's most awkward choose-your-own sex scene."--Amazon.